Fidelity of a peer‐led asthma self‐management intervention and its attention control in a multisite study of urban adolescents. Issue 2 (3rd December 2019) - Rhee, Hyekyun; Grape, Annette; Tumiel‐Berhalter, Laurene; Wicks, Mona; Sloand, Elizabeth; Butz, Arlene
Abstract: In this paper we compare the fidelity of a Peer‐Led Asthma Self‐Management Program for Adolescents (PLASMA) and its attention control. A randomized controlled trial involving two groups—the PLASMA group and the attention control group—was conducted between 2015 and 2018. Adolescents 12–17 years old ( N  = 259) in three cities in the United States received asthma self‐management education implemented at a day camp, followed by bi‐monthly, follow‐up contact for 12 months. Thirty‐five peer leaders and six adult educators implemented education sessions for the PLASMA and the attention control groups, respectively. The intervention was the peer‐led delivery of the content instead of the educational content itself. This study compares the extent to which the education sessions and follow‐up contacts were implemented in accordance with the study protocol by the peer and adult educators. Most topics on asthma knowledge and skills (85–95%) were delivered as intended at an adequate pace in both groups. Peer leaders missed more content in the psychosocial domain than adult educators—14% versus 0%, respectively ( t  = −3.7; p  = .010). PLASMA participants reported high content and time fidelity for all education sessions (94% to 97.6%). Greater success in bimonthly follow‐up contacts was reported in the attention control groups, with 4.6 ( ± 1.5) contacts on average compared to 2.6 (±2.02) in the PLASMA groups ( t  = 9.02; p  < .001). Most components of the asthma self‐management program were implemented with high fidelity in both groups. The relatively low fidelity in delivering psychosocial content and performing follow‐up contacts in the PLASMA groups underscores the need for intensive training to enhance peer leaders' competency with managing these aspects of PLASMA to maximize fidelity. Peer leaders can implement asthma self‐management educational components of the intervention with high fidelity similar to adult educators.